Mediation of motivated strategies for learning for thinking maps involvement towards metacognitive awareness / Nurul Nadia Hassan ... [et al.] - Hassan, Nurul Nadia; Hamzah, Siti Salbiah; Mohd Jalaluddin, Nurkhuzaimah Fazreen; Idris, Muhammad Zaffwan; Said5, Che Soh (Universiti Teknologi MARA, 2023)
This study emphasized the challenges involved in teaching and learning fundamentals of programming as a consequence of the lack of metacognitive awareness, which is associated with problem solving abilities. These abilities can be enhanced through the use of thinking maps, but they are typically used only in school and under the supervision of a teacher. Additionally, the practice is conducted in a typical manner, with no interesting features incorporated into the process, and it does not promote the development of metacognitive awareness. Thus, this study implementing the use of educational tool which embedding motivated strategies for learning theories including multimedia principles and elements called Motivated Strategies Thinking Maps Tool (MoSTMaT) and apply it experimentally in order to determine the tool's effectiveness towards guiding students in using thinking maps to solve fundamental programming problems. A total of 128 students participated in the quasi-experimental research. To compare the differences between groups, participants were given the Metacognitive Awareness Inventory (MAI) and the Motivated Strategies for Learning (MSLQ) questionnaires for pre- and post-testing. Appropriate analyses were performed to seek the relations among factors studied. The results indicated that motivated strategies for learning are indeed a mediating factor between the implementation of using thinking maps in learning and metacognitive awareness among computing students.